Melatonin Ameliorates Organellar Calcium Homeostasis, Improving Endoplasmic Reticulum Stress-Mediated Apoptosis in the Vastus Lateralis Muscle of Both Sexes of Obese Diabetic Rats - Diego Salagre; Miguel Navarro-Alarcón; Luis Gerardo González; Mohamed A. Elrayess; Marina Villalón-Mir; Rocío Haro-López; Ahmad Agil (Antioxidants)
Endoplasmic reticulum (ER) stress is a crucial factor in the progression of obesity-related type 2 diabetes (diabesity), contributing to skeletal muscle (SKM) dysfunction, calcium imbalance, metabolic inflexibility, and muscle atrophy. The ER and mitochondria together regulate intracellular calcium levels, and melatonin, a natural compound with antioxidant properties, may alleviate these challenges. Our previous research showed that melatonin raises intracellular calcium and preserves muscle structure by enhancing mitochondrial function in obese diabetic rats. This study further explores melatonin’s potential to reduce ER stress in the vastus lateralis (VL) muscle by modulating the unfolded protein response (UPR) and restoring calcium levels disrupted by diabesity. Five-week-old Zücker diabetic fatty (ZDF) rats and lean littermates of both sexes were divided into control and melatonin-treated groups (10 mg/kg/day for 12 weeks). Flame atomic absorption spectrometry results showed that melatonin restored VL intraorganellar calcium homeostasis, increasing calcium levels in mitochondria and reducing them in the ER by raising the activity and expression of calcium transporters in both sexes of ZDF rats. Melatonin also decreased ER stress markers (GRP78, ATF6, IRE1α, and PERK) and reduced pro-apoptosis markers (Bax, Bak, P-JNK, cleaved caspase 3 and 9) while increasing Bcl2 levels and melatonin receptor 2 (MT2) expression. These findings suggest that melatonin may protect against muscle atrophy in obese and diabetic conditions by mitigating ER stress and calcium imbalance, highlighting its therapeutic potential.